Isolamento e seleção de microrganismos de cana-de-açúcar com potencial de promoção de crescimento vegetal - Bezerra, Gabrielle Alves (2021)
Plant growth promoting microorganisms (PGPM) are known to establish positive relationships with plants. They can inhabit the soil, the rhizosphere and the interior of plant tissues, making up a large part of the plant microbiota. They act in favor of plant nutrition, with nitrogen fixation and/or mineral solubilization, in the production of phytohormones, in the control of pathogens, and/or in the promotion of plant tolerance to abiotic stresses. These microorganisms have provided positive results in several economically important crops and can act as an alternative to the use of chemical inputs, minimizing production costs and making agricultural practices more sustainable. Therefore, this work aimed to isolate and analyze microorganisms from soil, rhizosphere and sugarcane root endosphere, to prospect bacteria, fungi and yeasts with potential to promote plant growth. The samples were plated on NA (bacteria), PDA (filamentous fungi) and YEPD (yeast) medium. Morphologically distinct colonies were isolated in pure culture and analyzed for their ability to produce indoleacetic acid (IAA), solubilize phosphate and control the development of phytopathogen Fusarium verticillioides. A total of 281 isolates were obtained, 112 from the soil, 96 from the rhizosphere and 73 from the sugarcane root endosphere. A prevalence of bacteria (223 isolates) was observed, followed by filamentous fungi (60 isolates) and, finally, in a smaller number, yeasts (9 isolates). Among the mechanisms evaluated, there was a greater number of AIA producers isolated from the endosphere, a greater number of phosphate solubilizers isolated from the soil, and a greater number of antagonists to the phytopathogen isolated from the rhizosphere. Bacteria also stood out in all evaluated mechanisms, probably due to their prevalence in the studied environments. Few isolates showed more than one plant growth promotion mechanism. The ENDO26 bacterium, isolated from the endosphere, was the only one that showed positive results for the three growth promotion mechanisms. In addition to ENDO26, two other isolates were selected: SOL88, a yeast isolated from soil, which showed positive results for phosphate solubilization and AIA production, and RIZ85, a fungus isolated from the rhizosphere, which produced AIA and presented antagonism against the phytopathogen. These three isolates were evaluated on a plate with Arabdopsis thaliana, to verify their ability to promote plant development, however, they did not promote the plant growth in vitro. The identification of isolates and more in-depth tests with other plant species are necessary to verify the potential for using these strains as plant growth promoters.